The Development of An Active Learning Model Through Su Ji Pu Li Activities with Metaverse Media for The Topic of Buddhist History to Enhance Critical Thinking Skills Among First-Grade Dhamma Studies Students at The Secondary Level - Chaiprasert, Phra Suriya; Phumpuang, Kittipong; Sittiwong, Tipparat (Journal of Multidisciplinary in Humanities and Social Sciences, 2026)
This article aimed to: (1) investigate the existing learning conditions; (2) develop an active learning instructional model; (3) examine the effects of implementing the developed model; and (4) evaluate an active learning model using Su Ji Pu Li activities integrated with metaverse media on the topic of Buddhist history to enhance critical thinking skills among first-level Dhamma Studies students at the secondary level. This research employed a research and development (R&D) approach. The sample consisted of 30 first-level Dhamma Studies students from Kingphet School, Ratchathewi District, Bangkok. The research instruments included questionnaires, interview forms, a critical thinking skills assessment, and a student satisfaction questionnaire. Data was analyzed using mean, standard deviation, and inferential statistics through a dependent samples t-test. The results revealed that: (1) prior to the implementation of the instructional model, students’ critical thinking skills were at a moderate level; (2) the efficiency of the active learning instructional model was 86.30/92.50, indicating that it met the established criteria; (3) the students’ critical thinking skills after learning were significantly higher than before learning at the .05 level (t = 14.72), with the post-test mean score ( = 23.60, S.D. = 2.70) higher than the pre-test mean score ( = 15.20, S.D. = 2.95); and (4) the students’ satisfaction with the instructional model was at the highest level ( = 4.55, S.D. = 0.52).